Implementation of the sport education model to strengthen physical education students’ soft skills in higher education - Shutan Arie Shandi; Andi Eddy; Muhammad Ziaulhaq; Rabwan Satriawan; Firdaus Firdaus (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2026)
Strengthening soft skills is an essential objective of physical education in higher education, as prospective physical education teachers are required to demonstrate leadership, collaboration, and professional responsibility. The Sport Education Model (SEM) is a pedagogical approach that provides authentic learning experiences by engaging students as participants, coaches, referees, and team managers. This study aimed to analyze the implementation of SEM and its association with the development of soft skills among students in the Physical Education, Health, and Recreation (PJKR) program, given the limited studies examining SEM in Indonesian higher education. A qualitative descriptive method was employed with 60 students from STKIP Taman Siswa Bima as participants. Data were obtained through observations, interviews, and student reflection journals collected over one semester. The patterns of change in students' soft skills during the observation period were described by converting observation and reflection indicators into percentage distributions. The results showed that leadership (68%), teamwork (50%), communication (54%), responsibility (48%), and problem-solving (52%) each had a percentage pattern. These percentages represent the distribution of observed behaviors across the five soft-skill dimensions recorded during the learning period and indicate observable developments in leadership, teamwork, communication, responsibility, and problem-solving within the higher education context examined. The findings reveal patterns of collaborative interaction, role engagement, and interpersonal communication during the learning process, reflecting the presence of these five soft-skill dimensions. SEM is a contextually appropriate instructional approach for supporting these soft skills dimensions among physical education students in comparable higher education settings, based on the observed patterns.